Features psychological preparation of students - Горпініч Олексій Олександрович (Oleksij Gorpinich) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: presents the analysis of the impact of training melee fighting the physical and mental health of students of the Academy of Interior Ministry of Ukraine. Material and methods: the control group consisted of students of Polytechnic University, who did not have any (except for the mandatory physical education classes) exercise. Results: it is shown that training improves the melee fighting, both physical and mental health. However, first-year students, compared with their counterparts from the fourth year, the positive change is much less pronounced. Students without additional exercise positive changes very little. Conclusions: the use of anti-stress and social-psychological training in conjunction with exercise resulted in a significant increase in rates of physical and mental health of first-year students of the academy.